Authigenic illite within northern and central North Sea oilfield sandstones: evidence for post-growth alteration. (April 2014) - Wilkinson, M.; Haszeldine, R. S.; Fallick, A. E.
Abstract: It has been previously reported that late diagenetic fibrous illite, separated out from oilfield sandstones for dating by the K-Ar method, has systematically shown an increasing K-content with burial depth in the UK northern and central North Sea. This is surprising as fibrous illite is believed to form rapidly, in response to a geological event such as oil charging, and to retain its composition during subsequent burial. If the composition of the illite is related to present-day conditions, rather than the conditions of initial formation, then argon loss may have occurred, making K-Ar ages of questionable validity. Variations in crystal chemistry of the illite and their fundamental particle size and shape (length/width) distribution suggest alteration of the illite from the time of formation. The extent to which K-Ar ages of illite might need to be re-interpreted as a result of this post-formation alteration is not quantifiable at present; however there is evidence to suggest that the ages may be interpreted in terms of burial models involving both crystal nucleation and growth, and that a high proportion of Ar within the crystals may be retained during post-growth recrystallization.